2016
DOI: 10.5812/jjm.30412
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Streptococcus agalactiae Isolates From Pregnant and Non-Pregnant Women at Yazd University Hospital, Iran

Abstract: Background:Streptococcus agalactiae (Group B streptococcus, GBS) that colonize the vaginas of pregnant women may occasionally cause neonatal infections. It is one of the most common causes of sepsis and meningitis in neonates and of invasive diseases in pregnant women. It can also cause infectious disease among immunocompromised individuals. The distribution of capsular serotypes and genotypes varies over time and by geographic era. The serotyping and genotyping data of GBS in Iranian pregnant and non-pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Approximately most of GBS strains possess one of alp genes. Our multiplex PCR analysis results showed that the frequency of rib in GBS isolates was 40%, as predominant type that was similar to other geographical regions of Iran, Chinaand Italy [3, 37, 38]. Only 1% of the tested isolates were negative for any existing alp genes and 4% were positive for two genes.…”
Section: Discussionsupporting
confidence: 73%
“…Approximately most of GBS strains possess one of alp genes. Our multiplex PCR analysis results showed that the frequency of rib in GBS isolates was 40%, as predominant type that was similar to other geographical regions of Iran, Chinaand Italy [3, 37, 38]. Only 1% of the tested isolates were negative for any existing alp genes and 4% were positive for two genes.…”
Section: Discussionsupporting
confidence: 73%
“…However, it is different from a study conducted before three decades in the same hospital where 60% were type Ib followed by type Ia (16%) [37]; in Poland, serotype III (35%) was the most prevalent types followed by Ia (20%), V (17%), II (15%), Ib (8%) and IV (5%) [38]. Similarly, a study from Iran showed that serotype III (50%) was the most common serotype, followed by serotype II (25%), Ia (12%), V (11%), and Ib (2%) [39].…”
Section: Discussionmentioning
confidence: 99%
“…The ST and clonal complex (CC) of each isolate were determined using the GBS MLST database (http://pubmlst.org/sagalactiae/) and eBURST V3 (http://eburst.mlst.net/v3/enter_data/single/). VIII AGGTCAACCACTATATAGCGA TCTTCAAATTCCGCTGACTT cps8J [16] dltS AGGAATACCAGGCGATGAACCGAT TGCTCTAATTCTCCCCTTATGGC dltS [17] adhP GGTGTGTGCCATACTGATTT ACAGCAGTCACAACCACTCC adhP [17] pheS ATATCAACTCAAGAAAAGCT TGATGGAATTGATGGCTATG pheS [17] Atr ATGGTTGAGCCAATTATTTC CCTTGCTCAACAATAATGCC atr [17] glnA AATAAAGCAATGTTTGATGG GCATTGTTCCCTTCATTATC glnA [17] sdhA AACATAGCAGAGCTCATGAT GGGACTTCAACTAAACCTGC sdhA [17] glcK GGTATCTTGACGCTTGAGGG ATCGCTGCTTTAATGGCAGA glcK [17] Tkt ACACTTCATGGTGATGGTTG TGACCTAGGTCATGAGCTTT tkt [17] ermA AACTTGTGGAAATGAGTCAACGG CAGAATCTACATTAGGCTTAGGG ermA [19] ermB ATTGGAACAGGTAAAGGGCG GAACATCTGTGGTATGGCG ermB [19] mefA AGTATCATTAATCACTAGTGC TTCTTCTGGTACTAAAAGTGG mefA [19] gyrA GGTTTAAAACCTGTTCATCGTCGT GCAATACCAGTTGCACCATTGACT gyrA [20] parC CCGGATATTCGTGATGGCTT TGACTAAAAGATTGGGAAAGGC parC [20] https://doi.org/10.1371/journal.pone.0240590.t001…”
Section: Multi-locus Sequence Type and Clonal Complex Analysismentioning
confidence: 99%